2019
DOI: 10.1016/j.conctc.2019.100363
|View full text |Cite|
|
Sign up to set email alerts
|

Culturally-tailored text-messaging intervention for smoking cessation in rural American Indian communities: Rationale, design, and methods

Abstract: Background American Indian (AI) and Alaska Native (AN) communities experience disproportionately high rates of tobacco use when compared to the overall U.S. population, especially among rural populations. Methods We implemented a single-blind, randomized clinical trial of a text messaging-based smoking cessation intervention through the tobacco quitlines of five states (Alaska, Minnesota, New Mexico, Oklahoma, and Wisconsin) with high percentages of AI residents. We par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The need for flexibility in participant engagement strategies, and the ability to pivot based on community-generated solutions for health equity in substance use accessibility and capacity was, in fact, described across studies. For example, Orr and colleagues ( 47 ) initially intended to recruit AI/AN college students for their tobacco cessation program. However, recruitment efforts led to only 9 college students enrolling.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The need for flexibility in participant engagement strategies, and the ability to pivot based on community-generated solutions for health equity in substance use accessibility and capacity was, in fact, described across studies. For example, Orr and colleagues ( 47 ) initially intended to recruit AI/AN college students for their tobacco cessation program. However, recruitment efforts led to only 9 college students enrolling.…”
Section: Resultsmentioning
confidence: 99%
“…Out of the 20 studies reviewed, ten (50%) of them reported outcomes related to intervention effectiveness ( 1 , 34 , 36 , 38 , 40 , 41 , 45 , 48–50 ). There were several studies where the primary outcome was tobacco cessation [ n = 7; ( 32 , 36 , 38 , 45 , 47–49 )]. In a tobacco cessation program for pregnant Aboriginal women, self-reported 12-week 7-day point-prevalence abstinence was 13.6% ( 38 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations